2003
DOI: 10.1103/physrevb.68.214303
|View full text |Cite
|
Sign up to set email alerts
|

Elementary excitations in condensed oxygen (α,β,γ, liquid) by high-resolution Raman scattering

Abstract: Elementary excitations ͑magnon, libron, vibron, and their combinations͒ of solid and liquid oxygen samples of high optical quality have been investigated by high resolution Raman spectroscopy in the temperature range 10-90 K. From spectra we deduced band frequency, bandwidth, and band shape of all modes as a function of temperature. In particular we registered in a very narrow temperature range ⌬TϽ0.5 K at the ␣-␤ phase transition libron spectra of the ␣ phase as well as of the ␤ phase; from the coexistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Figure shows the oxygen vibron as a function of concentration at two different temperatures: at T = 14 K (Figure a) and at T = 42 K (Figure b). The true bandwidth of vibrons in pure oxygen is very narrow (<0.1 cm -1 , high-resolution Raman spectra of pure α-O 2 and γ-O 2 are plotted with broken lines in Figure ), whereas the resolution in our spectra of the mixed systems was ∼2 cm -1 . Therefore, the spectral features at higher temperatures (Figure b) must contain at least two contributions due to different surroundings (N 2 /O 2 ) or due to the doublet in pure γ-O 2 (1552 and 1553 cm -1 , intensity ratio 3:1).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Figure shows the oxygen vibron as a function of concentration at two different temperatures: at T = 14 K (Figure a) and at T = 42 K (Figure b). The true bandwidth of vibrons in pure oxygen is very narrow (<0.1 cm -1 , high-resolution Raman spectra of pure α-O 2 and γ-O 2 are plotted with broken lines in Figure ), whereas the resolution in our spectra of the mixed systems was ∼2 cm -1 . Therefore, the spectral features at higher temperatures (Figure b) must contain at least two contributions due to different surroundings (N 2 /O 2 ) or due to the doublet in pure γ-O 2 (1552 and 1553 cm -1 , intensity ratio 3:1).…”
Section: Resultsmentioning
confidence: 86%
“…The vibron spectrum of (N 2 ) 0.78 (O 2 ) 0.22 in Figure contains two bands at lower temperatures ( T < 39 K) and only one band at higher temperatures ( T > 39 K). The band at 1552.5 cm -1 is known from pure solid α-O 2 and β-O 2 , the band at 1555.5 cm -1 is known from matrix-isolated O 2 in α-N 2 . Therefore, the spectra at T < 32.5 K we assign to α*-O 2 (or β*-O 2 ) and α*-N 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, 16 O has a neutron absorption cross-section five times smaller than that of 2 H. In addition to phonons, solid oxygen (s-O 2 ) in its low temperature phases has strong magnetic interactions which could be harnessed for UCN production [18]. These magnetic excitations have been widely studied using Raman scattering [19,20] as well as neutron scattering [21][22][23]. It has been shown that the low temperature phases possess very different dynamics that often entangle translational, librational, and spin excitations through the orientation-dependent couplings between the diatomic oxygen molecules on the solid lattice sites.…”
Section: Introductionmentioning
confidence: 99%
“…We have identified an additional phenomenon of ␣-O 2 that is intimately connected with its magnetism: Twolibron excitations have been observed in our zero-pressure Raman measurements. 32 These we explained as originating with magnetic coupling of two molecules in the primitive cell performing librations. In our recent low-pressure Raman study 16 on ␣ oxygen we found that due to an enhancement of the spin coupling mechanism, the intensities of two-libron excitations increase by a factor of about 5 as one applies pressure from 0 to 1.25 GPa.…”
Section: Magnetism In the ␣ And ␦ Phasesmentioning
confidence: 94%